Is U.S. health care an appropriate system? A strategic perspective from systems science - Janecka Ivo P (BMC, 2009)
Abstract Context Systems science provides organizational principles supported by biologic findings that can be applied to any organization; any incongruence indicates an incomplete or an already failing system. U.S. health care is commonly referred to as a system that consumes an ever- increasing percentage of the gross domestic product and delivers seemingly diminishing value. Objective To perform a comparative study of U.S. health care with the principles of systems science and, if feasible, propose solutions. Design General systems theory provides the theoretical foundation for this observational research. Main Outcome Measures A degree of compliance of U.S. health care with systems principles and its space-time functional location within the dynamic systems model. Results of comparative analysis U.S. health care is an incomplete system further threatened by the fact that it functions in the zone of chaos within the dynamic systems model. Conclusion Complying with systems science principles and the congruence of pertinent cycles, U.S. health care would likely dramatically improve its value creation for all of society as well as its resiliency and long-term sustainability. Immediate corrective steps could be taken: Prioritize and incentivize health over care; restore fiscal soundness by combining health and life insurance for the benefit of the insured and the payer; rebalance horizontal/providers and vertical/government hierarchies.